Magnetic resonance imaging of intraductal papillomas: typical findings and differential diagnosis - Dietzel, Matthias; Kaiser, Clemens; Baltzer, Pascal A. T. (Journal of Computer Assisted Tomography, 2015)
Even upon core biopsy, accurate classification of benign intraductal papillomas (IPs) can be difficult. Accordingly, IPs are still frequently surgically resected. Therefore, accurate classification of IP by magnetic resonance mammography (MRM) would potentially optimize patient management. However, the few investigations assessing MRM of IP included small patient collectives, and overall accuracy is still unknown. We performed this investigation to analyze the morphologic and dynamic MRM profiles of IP in more detail and to identify the overall accuracy of MRM for differential diagnosis of IP versus malignant breast lesions.Consecutive patients scheduled for MRM (standardized scanning protocols: dynamic T1-weighted gradient echo before/after Gd-DTPA [gadolinium diethylenetriamine pentaacetate; 0.1 mmol/kg body weight]; T2-weighted turbo spin echo) with subsequent surgicopathologic verification were enrolled. For the detailed assessment of morphologic and dynamic profiles, 2 experienced radiologists (>500 MRM examinations; blinded to surgicopathologic verification) performed prospective evaluation of MRM, in consensus, applying 17 predefined MRM descriptors. From this database, all patients showing IP (n = 83) or malignant breast lesions (n = 648) were further evaluated statistically: univariate analyses (association of single descriptors with IP/breast cancer: contingency table statistics) and multivariate analyses were performed to identify accurate descriptor combinations (CHAID [CHi-squared Automatic Interaction Detection]) and overall accuracy of MRM for differential diagnosis of IP versus malignant breast lesions (logistic regression; receiver operating characteristics [ROC], area under the ROC curve).There were 82.4% of MRM descriptors significantly associated with IP (n = 14; P < 0.05). The accuracy of single descriptors (odds ratio [OR], <=10.6) could be further increased by descriptor combinations (double combination: OR <=12.7; triple combination: OR <=15.0). With area under the ROC curve = 0.90, there was a high overall accuracy of MRM for the differential diagnosis of IP versus malignant breast lesions.A detailed assessment of MRM allows precise characterization of benign IPs and accurate differentiation from malignant breast lesions.
EVALuna2:23003